Cost-effectiveness of early initiation of first-line combination antiretroviral therapy in Uganda - Sempa Joseph; Ssennono Mark; Kuznik Andreas; Lamorde Mohammed; Sowinski Stefanie; Semeere Aggrey; Hermans Sabine; Castelnuovo Barbara; Manabe Yukari C (BMC, 2012)
Abstract Background Ugandan national guidelines recommend initiation of combination antiretroviral therapy (cART) at CD4+ T cell (CD4) count below 350 cell/μl, but the implementation of this is limited due to availability of medication. However, cART initiation at higher CD4 count increases survival, albeit at higher lifetime treatment cost. This analysis evaluates the cost-effectiveness of initiating cART at a CD4 count between 250-350 cell/μl (early) versus <250 cell/μl (delayed). Methods Life expectancy of cART-treated patients, conditional on baseline CD4 count, was modeled based on published literature. First-line cART costs $192 annually, with an additional $113 for patient monitoring. Delaying initiation of cART until the CD4 count falls below 250 cells/μl would incur the cost of the bi-annual CD4 count tests and routine maintenance care at $85 annually. We compared lifetime treatment costs and disability adjusted life-expectancy between early vs. delayed cART for ten baseline CD4 count ranges from 250-350 cell/μl. All costs and benefits were discounted at 3% annually. Results Treatment delay varied from 6-18 months. Early cART initiation increased life expectancy from 1.5-3.5 years and averted 1.33-3.10 disability adjusted life years (DALY's) per patient. Lifetime treatment costs were $4,300-$5,248 for early initiation and $3,940-$4,435 for delayed initiation. The cost/DALY averted of the early versus delayed start ranged from $260-$270. Conclusions In HIV-positive patients presenting with CD4 count between 250-350 cells/μl, immediate initiation of cART is a highly cost-effective strategy using the recommended one-time per capita GDP threshold of $490 reported for Uganda. This would constitute an efficient use of scarce health care funds.